2018
DOI: 10.14202/vetworld.2018.1145-1149
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of bacteria from fresh guava (Psidium guajava) sold at local markets in Mymensingh and their antibiogram profile

Abstract: Aim:The study was conducted for the isolation, identification, and antibiogram of bacteria obtained from fresh guava (Psidium guajava).Materials and Methods:A total of 25 fresh guavas were collected from five markets located in Mymensingh city. Guava samples were cultured onto various selective media such as eosin methylene blue, xylose lysine deoxycholate, thiosulfate-citrate-bile salts-sucrose, blood agar, and mannitol salt agar for the isolation of bacteria. Biochemical tests (dextrose, maltose, lactose, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…Apart from orange juice collected at TN and RO and sugarcane juice sold by the vendors of TN, the presence of Vibrio contamination in our study areas were negligible. Previous studies also found the similar low Vibrio contamination of fruit juices when compared with E. coli and Salmonella contamination [24,42,43].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Apart from orange juice collected at TN and RO and sugarcane juice sold by the vendors of TN, the presence of Vibrio contamination in our study areas were negligible. Previous studies also found the similar low Vibrio contamination of fruit juices when compared with E. coli and Salmonella contamination [24,42,43].…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have reported the presence of AMR bacteria in apple and orange juice samples [21][22][23][24][25][26][27]. A recent study in India found 80% of the bacterial strains isolated from orange juice samples to be multi-drug resistant [28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, similar findings were recorded in a study on fresh fruit juices in Dhaka City, Bangladesh [55]. In another report, in Mymensingh District, Bangladesh, a total of 25 fresh-cut guava samples were collected, and a TVBC range of 6.47-6.62 log CFU/mL was detected in the fruit samples [34]. Similarly, the average TVBC range was 6.47 log CFU/g in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The present study evaluated the total microbial load on fresh fruits and vegetables (FFV) and concentrated on the safety of FFV by eliminating microorganisms. The indicator bacteria (TCC and TFC), the total viable bacteria (TVBC), and the total presence of fungi on the FFV surface reflect the sanitary nature of Agricultural products [34][35][36]. The isolated bacterial strains with higher TVBC were observed in studied fruits and vegetables (Tables 1 and 2), and similar findings were also obtained in other studies [46,47].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation